Conceptual Framework for Assessing and Measuring System Maturity, System Readiness and Capability Readiness - Tetlay, Abideen (INCOSE EuSEC 2010 with permission, 2010)
This study summarises the issues with the notions of "maturity" and "readiness" within the context of the System Development and overall Lifecycle and provides formal definitions for these terms. It explains why a Framework is required to assess and measure Maturity and Readiness and how the conceptual Framework was devised, including a process for applying the Framework for the assessment and measurement of System Maturity, System Readiness and Capability Readiness.
Keywords: System Maturity; System Readiness; Operational Capability; Capability Readiness; Measures of Effectiveness; Framework